Disrupted Spontaneous Neural Activity Related to Cognitive Impairment in Postpartum Women - Zheng, Jin-Xia; Chen, Yu-Chen; Chen, Huiyou; Jiang, Liang; Bo, Fan; Feng, Yuan; Tang, Wen-Wei; Yin, Xindao; Gu, Jian-Ping (Frontiers in Psychology, 2018)
Purpose: Prior research has demonstrated that the postpartum period is associated with an increased risk of cognitive impairment. This study aims to investigate whether disrupted spontaneous neural activity exists in postpartum women without depression using resting-state functional magnetic resonance imaging (rs-fMRI) and to detect the relationship between these abnormalities and cognitive impairment. Materials and Methods: Postpartum women (n = 22) were compared with age- and education-matched nulliparous women (n = 23) using rs-fMRI. We calculated the amplitude of low-frequency fluctuation (ALFF) and regional homogeneity (ReHo) values to evaluate spontaneous neural activity and detect the relationship between rs-fMRI data and cognitive performance. Results: Relative to nulliparous women, postpartum women had significantly decreased ALFF and ReHo values primarily in the left posterior cingulate cortex (PCC) and prefrontal cortex and increased ALFF values in left cerebellar posterior lobe. We found a positive correlation between the ALFF and ReHo values in the PCC and the complex figure test (CFT)-delayed scores in postpartum women (r = 0.693, p = 0.001; r = 0.569, p = 0.011, respectively). Moreover, the clock-drawing test (CDT) scores showed positive correlations with the ALFF and ReHo values in the right superior frontal gyrus (SFG; r = 0.492, p = 0.033; r = 0.517, p = 0.023, respectively). Conclusion: Our combined ALFF and ReHo analyses revealed decreased spontaneous neural activity, mainly in the PCC and prefrontal cortex, which was correlated with specific impaired cognitive functioning in postpartum women. This study may elucidate the neurophysiological mechanisms underlying postpartum cognitive impairment and enhance our understanding of the neurobiological aspects of the postpartum period.